2019
DOI: 10.3389/fnbeh.2019.00246
|View full text |Cite
|
Sign up to set email alerts
|

Lower Digit Ratio (2D:4D) Indicative of Excess Prenatal Androgen Is Associated With Increased Sociability and Greater Social Capital

Abstract: Positive social interactions are crucial for human well-being. Elevated prenatal exposure to testosterone as indicated by a low second-to-fourth finger length ratio (2D:4D) relates to more aggressive/hostile behavior in men of low 2D:4D, especially in challenging situations. How much people enjoy interacting with others is determined by the personality trait sociability. Given its role in approach and avoidance behavior, sociability might also be influenced by prenatal sex hormones, but studies are inconclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 88 publications
(138 reference statements)
1
10
0
Order By: Relevance
“…Similar to animal studies, the effect of high prenatal T concentration on the increased risk for anxiety-like behavior in females, but not in male offspring ( 21 , 73 , 74 ) was observed in humans ( 103 , 104 ). In one recent study, daughters of mothers with PCOS had a 78% risk increase of anxiety disorders compared to daughters of mothers without PCOS, whereas no significant increase in risk was observed in sons ( 103 ).…”
Section: Anxiety Disorderssupporting
confidence: 67%
See 1 more Smart Citation
“…Similar to animal studies, the effect of high prenatal T concentration on the increased risk for anxiety-like behavior in females, but not in male offspring ( 21 , 73 , 74 ) was observed in humans ( 103 , 104 ). In one recent study, daughters of mothers with PCOS had a 78% risk increase of anxiety disorders compared to daughters of mothers without PCOS, whereas no significant increase in risk was observed in sons ( 103 ).…”
Section: Anxiety Disorderssupporting
confidence: 67%
“…In one recent study, daughters of mothers with PCOS had a 78% risk increase of anxiety disorders compared to daughters of mothers without PCOS, whereas no significant increase in risk was observed in sons ( 103 ). In men, a low 2D:4D ratio was significantly associated with higher trait sociability, bigger personal social capital, and a larger personal social network size rather than social anxiety disorders ( 104 ). Together, these data support a sex-dependent effect of high prenatal T exposure, which increases the risk for anxiety disorders, particularly in adult women.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…This study investigated a possible association of 2D:4D and transsexuality in a large sample. It was part of the Finger Length in Psychiatry (FLIP) project 13 , 20 27 , a line of independent studies aiming to elucidate the role of prenatal sex hormone organization in the etiopathogenesis of psychiatric disorders in childhood, adolescence, and adulthood, such as addictive disorders 22 , 26 , 28 , 29 , 30 , suicide completion 31 , or behavioral symptoms in children 32 . Another goal was to establish prevention targets and strategies based on this model 33 .…”
Section: Study 1: New Original Datamentioning
confidence: 99%
“…The prenatal testosterone hormone calls the human mind and body an "organizational effect" before birth. The previous study reported, in men of low 2D:4D, elevated prenatal exposure to testosterone as indicated by a low digit ratio (2D:4D) refers to more aggressive/hostile behavior, especially in challenging situations [29]. Researchers Dyer et al, [30] found evidence that 2D:4D was a correlate of performance in an open skill sport in Basketball game.…”
Section: Discussionmentioning
confidence: 97%